2017
DOI: 10.1007/s13366-017-0337-7
|View full text |Cite
|
Sign up to set email alerts
|

Formally dual subsets of cyclic groups of prime power order

Abstract: We study the notion of formal-duality over finite cyclic groups of prime power order as introduced by Cohn, Kumar, Reiher and Schürmann. We will prove that for any cyclic group of odd prime power order, as well as for any cyclic group of order 2 2l+1 , there is no primitive pair of formally-dual subsets. This partially proves a conjecture, made by the priorly mentioned authors, that the only cyclic groups with a pair of primitive formally-dual subsets are {0} and Z/4Z. * Universität Rostock, robert.schueler2@u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…This conjecture has been verified when N is a prime power, by Schüler [21] for p odd or when N an even power of 2, and by Xia, Park, and Cohn [27] in the remaining cases, as well as when N is square-free.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…This conjecture has been verified when N is a prime power, by Schüler [21] for p odd or when N an even power of 2, and by Xia, Park, and Cohn [27] in the remaining cases, as well as when N is square-free.…”
Section: Introductionmentioning
confidence: 79%
“…Now we are ready to apply the methods already introduced; we will begin by providing two different proofs for the prime power case, one using the field descent method and one using the polynomial method. We emphasize that the polynomial method comprises of similar arguments as in [21], albeit with a different language. Theorem 6.1.…”
Section: The Prime Power Case Revisitedmentioning
confidence: 99%
“…We recall that when N is a prime power, Conjecture 1 has been proved in [20] and [24]. The author of [24] essentially showed that a primitive formally dual set in the cyclic group Z 2 2k with k ≥ 1 must have rank three.…”
Section: Primitive Formally Dual Sets With Small Rankmentioning
confidence: 99%
“…Motivated by this conjecture, some follow-up works studied formally dual pairs in cyclic groups. Specifically, this conjecture was proved for cyclic groups of prime power order, where Schüler confirmed the odd prime power case [10] and Xia confirmed the even prime power case [11]. Malikiosis showed that the conjecture holds true in many cases when the order of the cyclic group is a product of two prime powers [7].…”
Section: Introductionmentioning
confidence: 96%